Experimental testing of high performance fibre reinforced concrete deep beams - Smarzewski, Piotr; Poręba, Justyna; Rentflejsz, Agata (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The article presents the results of testing reinforced deep beams made of high performance concrete and fibre-concrete in the scheme of centrally placed load. The test was conducted for three deep beam elements of the of the main reinforcement bars in the form of lower, upper, horizontal and vertical stirrups in support areas of alternative reinforcement grids or steel and polypropylene fibers between the points of support elements. Analysis of results was based on the maps of major strains, the relations of force in the function of time and the relations of vertical displacements of the length of the members in the horizontal section.